The system and the mechatronics of a pagoda type micro-CMM - Fan, Kuang-Chao (2013)
This paper presents design considerations of a precision micro-CMM system and its mechatronic modules. The basic design concept is to meet the requirements of high stiffness, force balance, thermal balance, Abbe principle, metrology frame and vibration-free. Based on these criteria, a novel bridge of pagoda shape is designed and analysed by optimisation to verify its superior stiffness with force balance and thermal balance structure due to its symmetrical geometry. A high precision Z-ram design with co-axial counterweight and vibration suppression is presented. The design of a novel symmetrical coplanar XY-stage that observes the Abbe principle is explained. This micro-CMM has a measurement range of X: 20 mm, Y: 20 mm and Z: 10 mm. Driven by a commercial ultrasonic motor and fed back by a designed diffraction interference scale, each axis can achieve long stroke and nano-positioning motion. Adding a designed contact scanning measuring probe to the spindle, this system is able to measure any geometry of a part to nanometre resolution.